PENGARUH PENGGUNAAN UANG ELEKTRONIK DAN TEMAN SEBAYA TERHADAP PEMBELIAN IMPULSIF PADA SISWA SMAN 10 SURABAYA - Bagus Saputro, Andik; Ulfa Kamalia, Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of the modernization era is characterized by rapid technological changes that change individual consumption patterns. This problem is evidenced by pre-research that shows changes in individual consumption patterns, especially school students. This study aims to analyze the effect of the use of electronic money and peers on impulse purchases in SMA 10 Surabaya students. This study uses a quantitative approach with data collection techniques through distributed questionnaires. The sample of this study amounted to 199 grade 10 students of SMAN 10 Surabaya. The data of this study was analyzed using multiple linear regression with the help of SPSS version 22 tool. The results of the study showed that partially the use of electronic money and peers had a positive and significant effect on impulsive buying. This influence occurs due to technological changes that make it easier for individuals to carry out purchasing activities using electronic money, by using electronic money can increase efficiency in transactions. In addition, the influence of social pressure from the peer environment provides support or positive assessment of a certain form so that the individual will be encouraged to follow his peer group. This pattern is followed by the goal of individuals gaining recognition for their peer groups and maintaining a social image in their friendship environment. The novelty in this study lies in the research object that focuses on high school students.